The Effect of the Project-Based Learning Model on Improving Elementary School Students Learning Motivation and Critical Thinking Skills - Mirna Sentya; Alfiyyah Nurhidayah; Nurul Rofika; Tarman A Arif (STKIP Taman Siswa Bima, 2025)
This study aims to determine the effect of the project-based learning (PjBL) model on the learning motivation and critical thinking skills of fourth-grade students in social studies at UPT SDN 23 Centre Takalar 1. According to Afriana, et al, (2016), the PJBL model is a learning model that uses projects as the core of learning. This study employs a quasi-experimental method with a one-group pretest-posttest design. The sample consists of 30 fourth-grade students who were exposed to the PjBL learning model. Learning motivation data was collected through a validated questionnaire, while critical thinking skills were measured using pretest-posttest questions relevant to the topic of population search. Data were analyzed using normality, homogeneity, and T-tests to determine significant differences between pretest and posttest scores. The results showed a significant increase in students' learning motivation, with the average score rising from 58.447 to 84.76 (p = 0.000), and in their critical thinking skills, with the average score increasing from 60.230 to 79.450 (p = 0.000). The application of the PjBL learning model provides a contextual and challenging learning experience, enabling students to become more active, motivated, and capable of critical thinking in completing real-world projects. Thus, the project-based learning model is effective in enhancing students' learning motivation and critical thinking skills in social studies for fourth-grade elementary school students.